The Urgency Of Understanding And Practicing Pancasila Values As The State Foundation For The Young Generation - Putu Laksmi Danyathi, Ayu; Griadhi, Ni Made Ari Yuliartini; Nurcahyo, Edy (CV. Inara, 2022)
This study aims to determine the urgency of understanding and practicing Pancasila values as the basis of the state for the younger generation and to find out how to improve them. This research is qualified as a normative legal research using the approach of legislation, facts and analysis and legal concepts. The analysis technique uses descriptive, evaluation and argumentation techniques. The results obtained that the urgency of understanding and practicing the values of Pancasila as the basis of the state is very important because the younger generation is very vulnerable to the entry of values that are contrary to Pancasila. The number of cases among the younger generation that reflects the existence of radicalism, individualism, and taking actions that are contrary to the values of Pancasila. Efforts that can be made to improve understanding and practice of Pancasila values as the basis of the state in the younger generation can be carried out starting from the simplest instilling the values and implementing Pancasila values in the family environment, and then at the education level by including subjects about Pancasila and can also be done by socializing the planting of Pancasila values through social media.